Sistem Informasi Pengajuan Cuti Polmanbabel Berbasis Website - Dwi Fadilah; Riki Afriansyah; Yang Agita Rindri (Manutech : Jurnal Teknologi Manufaktur, 2023)
Paid Leave is one of the rights of worker for their absence from office due to different reasons such as sickness, marriage, vacation, or personal time and employees still receive regular wages during their absence from work in a certain period of time. Nowadays, in Polman Babel the paid leave system is still doing manually by filling out the paid leave application form provided by each work unit. After filling out the form, the relevant employees must submit the form to its each head of unit and then wait for confirmation for several days to find out the status of the submitted paid leave application. Every incoming paid leave application data is still not computerized well then it takes a long time to manage the data. To overcome this problem, researchers intend to develop a Website-Based Polmanbabel Paid Leave Submission System that can simplify and save time in making paid leave applications. To obtain data, researchers used observation techniques and interviews directly to related parties. System design is made using the waterfall method because it has a systematic and sequential approach. The stages of the waterfall method are requirements analysis, design, code and testing. The result of this research is a website-based paid leave application information system that can facilitate users in applying for paid leave, accepting or rejecting paid leave applications and viewing paid leave history that has been submitted by related workers before. System testing uses the black box testing method with the result that 100% of the system can run well and user acceptance testing with the result that 89.6% of users strongly agree with this system.